(untitled) (CIPEEX, 2025)
FLXControl is a web application designed to streamline the management of transportation documents (CTEs) for logistics companies. The system allows users to register and consult detailed information on CTEs, such as destination, value, client, state (UF), weight, driver, vehicle license plate, and financial data like driver payments, discounts, and tonnage rates. The backend will be implemented using *TypeScript* with the *Express* framework, chosen for its static typing and robustness in developing scalable and secure APIs. The frontend will be built using *TypeScript* with the *Next.js 14* framework, focusing on a modern and optimized interface. Styling will be handled with *Chakra UI, ensuring a responsive and easily customizable user interface. The project will follow **IT governance* principles based on *ITIL* and *COBIT* frameworks, ensuring system security, reliability, and scalability to handle large volumes of CTE data. Future plans include mobile app integration and extended functionalities for real-time data tracking and reporting. The development will be monitored through *KPIs* and visualized on *real-time dashboards* using Power BI.*KEYWORDS:* TypeScript; Express; Next.js; Chakra UI; Web Application; CTE; Backend; Frontend; IT Governance; Power BI; Logistics Management.